Analysis of the Principle of Utilitarianism in Judicial Decision-Making: A Study of Constitutional Court Decision Number 135/PUU-XXII/2024 Regarding the Separation of National and Regional Elections - Aisyah, Siti; Fitriani Wulandari, Dina (Judge : Jurnal Hukum, 2025)
This research analyzes the application of the principle of utilitarianism in the legal considerations of the Constitutional Court Decision Number 135/PUU-XXII/2024, which stipulates the separation of the organization of National Elections and Regional Elections starting in 2029. The simultaneous five-box election system implemented since 2019 has created a systemic burden for voters and organizers, increased the number of invalid votes, and resulted in the deaths of election officials due to extreme fatigue. This decision is a constitutional response to the complexity of simultaneous elections, which are considered to contradict the principles of popular sovereignty and the principles of honest and fair elections. The research method used is normative juridical with a legislative, conceptual, and case approach, which is analyzed qualitatively based on the theoretical framework of utilitarianism by Jeremy Bentham and John Stuart Mill. The research results show that the Constitutional Court's considerations in this decision reflect the application of the principle of "the greatest happiness for the greatest number" thru efforts to maximize collective happiness while minimizing excessive electoral burdens. Separating national and regional elections by a two-year gap has the potential to improve the quality of democratic participation, reduce systemic fatigue for organizers, strengthen the institutionalization of political parties, and increase political accountability at every level of government. From a utilitarian perspective, this decision demonstrates a long-term consideration for the sustainability of Indonesia's democratic system by prioritizing broader social utility over immediate interests, although its implementation requires a comprehensive legal transition design to avoid office vacancies and uphold the principle of power periodicity.